Duh -37 Because 37-9 is 37 and so the answer is -37
Answer:
Theres more orange juice than pineapple juice.
Step-by-step explanation:
Answer:
email or call or talk to your teacher and ask why
Step-by-step explanation:
Answer:
1/3 is the simplified form for given expression.
Step-by-step explanation:
Given that:
=![\sqrt[-3]{27}](https://tex.z-dn.net/?f=%5Csqrt%5B-3%5D%7B27%7D)
By simplifying:
Radical sign will be removed as follows:
= ![27^{-1/3}](https://tex.z-dn.net/?f=27%5E%7B-1%2F3%7D)
For removing the "-" sign from power, base will be inverted:
= ![(1/27) ^ {1/3}](https://tex.z-dn.net/?f=%281%2F27%29%20%5E%20%7B1%2F3%7D)
27 can also be written as 3 * 3 * 3 = 3^3
So,
= ![(1/3^3)^{1/3}](https://tex.z-dn.net/?f=%281%2F3%5E3%29%5E%7B1%2F3%7D)
= ![1^{1/3} / 3^{3* 1/3}](https://tex.z-dn.net/?f=1%5E%7B1%2F3%7D%20%2F%203%5E%7B3%2A%201%2F3%7D)
By simplifying we get:
= 1/3
i hope it will help you!
Answer:
x = ![\frac{g-f}{h-e}](https://tex.z-dn.net/?f=%5Cfrac%7Bg-f%7D%7Bh-e%7D)
Step-by-step explanation:
Given
f - ex = g - hx
Collect the terms in x on the left side by adding hx to both sides
hx - ex + f = g ( subtract f from both sides )
hx - ex = g - f ← factor out x on the left side
x(h - e) = g - f ← divide both sides by (h - e)
x = ![\frac{g-f}{h-e}](https://tex.z-dn.net/?f=%5Cfrac%7Bg-f%7D%7Bh-e%7D)